Exploring the curriculum development in content and language integrated learning: A systematic review - Lingli Li; Fuquan Huang; Siyu Chen; Leiqiong Pan; Wenjie Zeng; Xiaoqi Wu (Institute of Advanced Engineering and Science, 2020)
Content and language integrated learning (CLIL) is a booming innovation pervading many educational settings. The global spread of CLIL is being practiced in classrooms the world over. Nevertheless, there is still a lack of systematic curricula for CLIL, despite its widespread adoption. Furthermore, the majority of teachers are implementing CLIL without the support of suitable published materials or resource banks. To explore and explain the curriculum development in CLIL, 281 studies from 2009 to 2019 were reviewed systematically, focusing on peer-reviewed English-language journals. We identified studies through using 'Content and Language Integrated Learning' and CLIL as the search terms in the ProQuest Research Library and EBSCOhost databases. Selected articles were organized into five inquiry areas and analyzed thematically, inspired by the curriculum development model proposed by Pawlas and Oliva: 1) CLIL philosophy; 2) CLIL goals; 3) CLIL plan; 4) CLIL implementation; and 5) CLIL evaluation. Based on these themes, Boyer's scholarship of integration was introduced to propose a holistic model for CLIL curriculum development.